THE INFLUENCE OF TRADITIONAL MEDIA ON YOUNG PEOPLE IN SERBIA IN THE ERA OF DIGITAL TECHNOLOGIES - Selenić, Uroš (Sociološki godišnjak, 2023)
The main hypothesis of this study aimed to investigate the decreasing interaction of young individuals with traditional media in the era of digital technologies. The research involved 300 students from various higher education institutions in Serbia, who responded to six sets of questions. The first four sets employed the Likert scale method, while in the fifth and sixth sets, students provided open-ended responses to specific questions. Based on the obtained results, it was evident that traditional media have a limited influence on the younger generation and are not their primary source of information. Thus, the findings confirm assertions that the principal drivers for the current changes in daily habits are the emergence of the internet, social media, and the general advancement of digital technologies.